Oxidative burst response to monosodium urate crystals in patients with Behcet's syndrome - (:unkn) unknown (CLINICAL & EXPER RHEUMATOLOGY, 2005)
Objective. An erythematous response to intradermal injection of monosodium. urate crystals (MSU) has been demonstrated ill Behcet's syndrome (BS). To further elucidate the pathogenesis of this response, the effects of MSU on in vitro oxidative burst reaction of neutrophils and monocytes were investigated. Methods. Peripheral blood mononuclear cells from patients with Behcet's syndrome (BS), rheumatoid arthritis (RA), familial Mediterranean fever (FMF) and healthy controls (HQ were incubated with 100 ng/ml phorbol myristate acetate (PMA) and MSU at different dosages (25-500 mu g/ml). Oxidative burst reaction was evaluated in neutrophils and monocytes by flow cytometry. Results. In patients with BS, oxidative burst of neutrophils was significantly increased compared to HC at 125 mu g/ml and 250 mu g/ml dosages of MSU (1):! 0.001 and 0.004 respectively). In patients with FMF there was also an increased oxidative burst reaction at 75 mu g/ml, 250 g/ml and 500 mu g/ml (p <= 0.007; 0.001 and 0.004 respectively). In patients with BS, oxidative burst of monocytes was increased only at 125 mu g/ml dosage of MSU (p <= 0.002). However ill patients with FMF monocyte burst response was increased at 25 mu g/ml, 75 mu g/ml and 125 g/ml (p <= 0.004; < 0.0001; < 0.0001 and 0.002 respectively). In RA group, stimulation with PMA resulted ill a higher oxidative burst reaction than FMF and BS (1) 50.000 and p <= 0.008). No correlation was observed between oxidative burst of neutrophils or monocytes and intradermal responses to MSU crystals. Conclusion. Oxidative burst reaction with MSU is augmented in neutrophils and monocytes of BS. However the response is not specific and is unassociated with skin dermal test which has a high specificity for BS.
Keywords: Behcet's syndrome; oxidative burst reaction; monosodium urate crystals; urate skin test; FAMILIAL MEDITERRANEAN FEVER; NECROSIS-FACTOR-ALPHA; SUPEROXIDE GENERATION; MONOHYDRATE CRYSTALS; IN-VITRO; DISEASE; INFLAMMATION; MACROPHAGES; PATHERGY; ADHESION